Best Answer

3s + 4t + 2s + 5s + 6t

Group all of the like 's' terms & 't' terms together:

(3s+2s+5s) + (4t + 6t)

10s + 10t or 10(s+t)

Q: What is 3s plus 4t plus 2s plus 5s plus 6t equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

7s + 4t

4t = 24 Therefore t = 24/4 t = 6

10t=6t+24 -6 -6 4t=24 4 4 1=6 t=6

75+2t=100-2t 4t=25 t=6.25 So t is 6.25 or 25/4.

Heyy, For this question, we first need to add 2t to both sides of the equation to get: 75 + 4t = 100 Now, subtract 75 from both sides of the equation to get: 4t = 25 At this time, divide both sides by 4 to get t alone and get: t = 25 / 4 OR 6.25 FINAL ANSWER = t=6.25

Related questions

math

7s + 4t

If 4t + 5 = 37, then t = 8.

9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer

2

NEVERMIND!

It is an equation and the value of t is 1

T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed. t+(3-2t)=4t+1 3-t=4t+1 2-t=4t 2=5t last step is yours

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1

t in this problem equals -3. 4t- 8+ 25= 5 -25 -25 4t- 8= -20 +8 +8 4t= -12 /4 /4 t= -3

4t + 13t + 2 = 17t + 2

t + 10 - 4t = -11 Subtract 10 from each side: t - 4t = -21 ie -3t = -21 t = -21/-3 t = 7.